The Need to Strengthen Medicolegal System of Nepal : A Forensic Medicine Perspective - Atreya, Alok; Subedi, Nuwadutta (Journal of Nepal Health Research Council, 2025)
Forensic medicine offers important medical evidence for the purpose of criminal justice through examinations of victims, accused, and deceased. However, Nepal faces severe deficiencies in forensic services due to lack of trained specialists, which hampers justice delivery. Most medico-legal autopsies are performed by untrained doctors without forensic pathology expertise, who fail to recognize evidence. Facilities lack basic autopsy equipment, cold storage, and hygiene. Shortage of experts causes heavy workloads, which further affects the quality. There are also no guidelines for clinical forensic examinations. The poor state of mortuaries and flawed autopsies allow perpetrators to escape sentences. Urgent reforms like recruiting specialists, upgrading infrastructure, implementing forensic protocols, monitoring standards, and budget allocations are needed to strengthen Nepal’s medico-legal framework. The medico-legal system must leverage the expertise of local forensic experts by providing training, and career opportunities. Emphasis on forensics will be in the interests of justice, human rights and law. The time to act is now. Keywords: Autopsy; forensic medicine; medico-legal; Nepal.